ANALISIS REPRESENTASI PERBEDAAN RESPON TRAUMA PADA KORBAN BULLYING DALAM DRAMA KOREA “WEAK HERO CLASS 1” - Firda Wati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the differences in trauma responses among bullying victims as portrayed in the Korean drama Weak Hero Class 1. Using a descriptive qualitative approach, the research examines the main characters as psychological representations of school violence victims. The theoretical framework includes Bessel van der Kolk’s (2014) concept of trauma, the fight–flight–freeze–fawn trauma response model proposed by Walker (2013), and Judith Herman’s (1992) stages of trauma recovery. The analysis reveals that Yeon Si Eun exhibits a fight response characterized by extreme self-control and rationality as a form of self-protection; Oh Beom Seok demonstrates a fawn response that later transforms into aggression due to unresolved trauma; meanwhile, Ahn Soo Ho shows a progression from freeze to fight, eventually moving toward reconnection through empathy and social support. The study concludes that trauma resulting from bullying is complex, it can generate different defense patterns in each individual depending on their emotional history and the social support they receive. Weak Hero Class 1 offers a profound depiction of how trauma shapes adolescents’ behavior, relationships, and pathways to recovery.